Exposure-response analyses of venetoclax combined with hypomethylating agents in myelodysplastic syndromes: a retrospective study - Ji-Xin Tian; Ping Zhang; Xiao-Xu Wang; Jin-Wen Li; Dong-Xue Liu; Yi-Ying Liu; Zhi-Jian Xiao; Wen-Juan Miao (Frontiers in Pharmacology)
BackgroundVenetoclax (VEN), an orally bioavailable B-cell lymphoma-2 inhibitor, shows promising activity in patients with myelodysplastic syndromes (MDS) when combined with hypomethylating agents (HMAs). However, research regarding the VEN exposure in Chinese patients with MDS remains notably sparse.MethodsThis study retrospectively collected the predose (C0) and 6 h post-oral dosing plasma concentration (C6) of VEN for exposure-response analyses, using graphical analysis, receiver operator characteristic (ROC) curves, and logistic regression. Sixty-four patients were included in the exposure-safety analyses. Thirty-nine patients who were treated with HMAs as first-line treatment and added VEN within 4 cycles, or received VEN + HMAs as the initial treatment, were included in the exposure-efficacy analyses.ResultsIn Chinese MDS patients, the average C0 and C6 of VEN were 1990.60 ± 1,591.12 ng/mL and 2,966.66 ± 1,406.96 ng/mL, respectively, with large interindividual variability. The use of azole antifungals was a significant factor influencing VEN concentration (P < 0.05). Compared to VEN 400 mg administered without azole antifungals, concomitant use of azole antifungals with VEN 100 mg resulted in a 100.03% and 18.50% increase in VEN C0 and C6, respectively. In the efficacy analyses, the combination of VEN and HMAs achieved an overall response rate of 69.23%. Based on logistic regression and ROC curve analyses, the peak plasma concentration of VEN, without dose normalization, exhibits a significant correlation with treatment success (P < 0.05). Other factors, including C0, demographics, and disease characteristics (e.g., molecular mutations, baseline grade III/IV neutropenia, and prior therapies), were not associated with the probability of marrow remission. In the safety analyses, higher VEN concentrations were not associated with an increased probability of grade ≥3 infection or a more serious decrease in platelets and neutrophils.ConclusionThis study offers a preliminary exploration of the potential exposure-efficacy and exposure-safety relationships of VEN combined with HMAs for the treatment of MDS in Chinese patients. Given the interindividual variability in VEN exposure, therapeutic drug monitoring is recommended as an essential part of clinical practice in MDS treatment. Future research is necessary to conduct more in-depth and large-scale analyses to determine the optimal exposure threshold for VEN.